Model system for DNA replication of a plasmid DNA containing the autonomously replicating sequence from Saccharomyces cerevisiae. - Ishimi, Y (1993)
A negatively supercoiled plasmid DNA containing autonomously replicating sequence (ARS) 1 from Saccharomyces cerevisiae was replicated with the proteins required for simian virus 40 DNA replication. The proteins included simian virus 40 large tumor antigen as a DNA helicase, DNA polymerase alpha.primase, and the multisubunit human single-stranded DNA-binding protein from HeLa cells; DNA gyrase from Escherichia coli, which relaxes positive but not negative supercoils, was included as a "swivelase." DNA replication started from the ARS region, proceeded bidirectionally with the synthesis of leading and lagging strands, and resulted in the synthesis of up to 10% of the input DNA in 1 h. The addition of HeLa DNA topoisomerase I, which relaxes both positive and negative supercoils, to this system inhibited DNA replication, suggesting that negative supercoiling of the template DNA is required for initiation. These results suggest that DNA replication starts from the ARS region where the DNA duplex is unwound by torsional stress; this unwound region can be recognized by a DNA helicase with the assistance of the multisubunit human single-stranded DNA-binding protein.